Healthy Living: Keep Track of Your Blood Pressure - Leigh Ann Martin (EDIS)
Revised! FCS8601, a 1-page handout by Leigh Ann Martin, provides a convenient table for recording blood pressure readings for better blood pressure management. Published by the UF Department of Family Youth and Community Sciences, October 2009.